Features of the functioning of regional airports in the context of the development of the Russian air transportation market - I. N. Rykova; A. A. Alaev; R. S. Gubanov (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. The article examines the current state and factors of the development of the air transportation market in the context of new approaches to the organization of the creation and operation of airport infrastructure.Goal. To diagnose the modernization of Russian airports and search for factors of economic growth of regional air carriers. The analysis of statistical ﬁgures shows the need to attract government support measures to ﬁnance the ﬁxed assets of regional airports.Materials and methods. The applied methods of monographic and economic-statistical analysis, rating assessment provided the identiﬁcation of patterns of changes in the results of airport operations. An assessment and diagnosis of the means of state support for national airports at the expense of budget subsidies from Russia is given. The structure of accounts receivable of regional air carriers is presented and the prerequisites for its involvement in turnover to increase free cash ﬂow in the organization of air transportation are identiﬁed. The systematization of the data on the rating of national airports in the Russian Federation made it possible to determine the competitive positions of air carriers in the external market environment.Results and discussion. As a result of the study, conclusions were formulated on the need to identify and use reserves of economic growth, including new methods of distributing funds in the provision of services by regional airports. The sustainability of the development of regional airports will have a positive impact on the outbound and inbound tourism market.Conclusion. Optimizing the operating costs of regional airports in combination with regulating the seasonality of air travel is aimed at increasing the eﬀects of scale and balancing supply and demand in the air services market.